The Influence of the Transformational Leadership of the Headmasters on the Professional Development of Preschool Teachers - Zuriani Hanim Zaini; Mahaliza Mansor (Universitas Negeri Yogyakarta, 2021)
The purpose of this research is to study the influence of the transformational leadership of the headmasters on the professional development of national preschool teachers in Perak state. The design of this study is quantitative descriptive using questionnaires as the instrument. The sample consists of 260 national preschool teachers from Perak, Malaysia. The research instrument is adapted from Leadership Practice Inventory (LPI) and Readiness, Planning, Training, Implementation and Maintenance (RPTIM) Model. The findings showed that the level of the transformational leadership of the headmasters and the level of preschool teachers’ professional development are high. Pearson correlation analysis showed a significant positive relationship between these two variables. The regression analysis showed a high percentage of transformational leadership contributing to the preschool teachers’ professional development. In conclusion, transformational leadership of the headmasters has evidently influenced the professional development of preschool teachers. It supports the views that transformational leadership is an ideal leadership style to be practiced by the school leaders.